Time estimation for mating peak and calving of Bali cattle in semi-arid area in Netemnanu village Kupang district - Marianus Yakobus Magul Datur; Tarsisius Considus Thopianong; Nancy Diana Federika Katarina Foeh; Cynthia Dewi Gaina (Ovozoa: Journal of Animal Reproduction, 2023)
Bali cattle have advantages in terms of adaptation and fertilization rates, but tend to have slow growth rate because the rearing system is still grazing so that livestock growth becomes uncontrollable. This study aims to determine the peak of mating and calving estimation of Bali cattle (Bos sondaicus) that did not experience reproductive disorders, aged 4-7 years, belonging to smallholder farmers. The cattle were reared in semi-arid area of Netemnanu village, South Amfoang district, Kupang regency, Nusa Tenggara Timur. The method used was interviews with farmers, diagnosis of pregnancy through rectal palpation and ultrasonography. The results showed that the pregnancy rate was 86.20% (50/58).  Based on pregnancy data, it was known that the peak of mating would occur in December 2021 and estimated calving would reach its peak in September 2022.